Different Ways to Get There: Evidence of a Variable Female Sexual Response Cycle. Issue 7 (2nd September 2019) - Leavitt, Chelom E.; Leonhardt, Nathan D.; Busby, Dean M.
Abstract : Research has suggested women's sexual response cycle may vary more than previously thought. We asked 769 sexually active women between the ages of 18–70 to report on their sexual desire and arousal patterns during their last sexual experience. Using a latent class mixture model from retrospective sexual response data, we found six classes of desire and arousal patterns (Low, Middle Steady, High Fluctuation, Low Fluctuation, Upper Steady, High). We examined how these patterns were related to demographics, outcomes during the sexual experience, and outcomes for the global relationship. The Low sexual response class (8% of women) was significantly different from other classes in duration of the sexual experience, orgasms, and overall satisfaction with the sexual experience. Most sexual response patterns were associated with healthy relational and sexual outcomes. All classes except for the Low arousal and desire class showed associations with a neutral or positive sexual satisfaction evaluation. The non-problematic variation of women's sexual experience is an important concept to consider as it impacts determinations of dysfunction and women's self-evaluations. Not all women need to experience high levels of arousal throughout the sexual experience or to have desire at the outset in order to have positive sexual experiences and sexual outcomes.